A micromechanical comparison of human and porcine skin before and after preservation by freezing for medical device development - Ranamukhaarachchi, S. A.; Lehnert, S.; Ranamukhaarachchi, S. L.; Sprenger, L.; Schneider, T.; Mansoor, I.; Rai, K.; Häfeli, U. O.; Stoeber, B. (Scientific reports, 2016)
Collecting human skin samples for medical research, including developing microneedle-based medical devices, is challenging and time-consuming. Researchers rely on human skin substitutes and skin preservation techniques, such as freezing, to overcome the lack of skin availability. Porcine skin is considered the best substitute to human skin, but their mechanical resemblance has not been fully validated. We provide a direct mechanical comparison between human and porcine skin samples using a conventional mechano-analytical technique (microindentation) and a medical application (microneedle insertion), at 35% and 100% relative humidity. Human and porcine skin samples were tested immediately after surgical excision from subjects, and after one freeze-thaw cycle at −80 °C to assess the impact of freezing on their mechanical properties. The mechanical properties of fresh human and porcine skin (especially of the stratum corneum) were found to be different for bulk measurements using microindentation; and both types of skin were mechanically affected by freezing. Localized in-plane mechanical properties of skin during microneedle insertion appeared to be more comparable between human and porcine skin samples than their bulk out-of-plane mechanical properties. The results from this study serve as a reference for future mechanical tests conducted with frozen human skin and/or porcine skin as a human skin substitute.